Penentuan Nilai Konsentrasi Hambat Minimum (KHM) dan Konsentrasi Bunuh Minimum Minyak Daun Cengkeh (Syzygium Aromaticum) terhadap Propionibacterium acnes: Determination of Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) of Clove Leaf Oil (Syzygium Aromaticum) against Propionibacterium acnes - Yoan Dasawanti; Candrika Candrika (LPPM Universitas Abdurrab, 2025)
Infectious diseases are conditions caused by the entry of microorganisms into the body, leading to illness. One of the causes of infection is the bacterium Propionibacterium acnes. Continuous use of antibiotics can lead to resistance, thus alternative treatments such as the use of natural substances are needed. One of these alternatives is clove leaf. Clove leaves contain essential oil ranging from 1-4%, with eugenol as the main component. Eugenol has pharmacological activity as both an antimicrobial and anti-inflammatory agent. This study aims to determine the antibacterial activity of clove leaf oil against Propionibacterium acnes, specifically in determining the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC). Clove leaf oil was obtained through water distillation with a yield of 2.88%. The MIC test was performed using the agar diffusion method, while the MBC test was conducted using the streaking method. The results showed that clove leaf oil exhibits antibacterial activity that increases with increasing concentration. The MIC was obtained at a concentration of 5 mg/mL with a zone of inhibition diameter of 8.13 mm, while the MBC was at a concentration of 20 mg/mL. This antibacterial activity is attributed to the eugenol content in clove leaf oil, which can damage bacterial cell membranes and increase intracellular protein leakage. These findings indicate that clove leaf oil has potential as an effective natural antibacterial agent against Propionibacterium acnes and could serve as an alternative herbal treatment. Keywords: Clove leaf oil , KHM, KBM, Propionibacterium acnes